Analysis of Enterococcus faecalis in samples from Turkish patients with primary endodontic infections and failed endodontic treatment by real-time PCR SYBR green method (Journal of Applied Oral Science, 2009)
OBJECTIVE: The aims of this study were to investigate the presence of Enterococcus faecalis in primary endodontic infections and failed endodontic treatments using real-time PCR and to determine the statistical importance of the presence of E. faecalis in a Turkish population with endodontic infections. MATERIAL AND METHODS: E. faecalis was investigated from 79 microbial samples collected from patients who were treated at the Endodontic Clinic of the Dental School of Atatürk University (Erzurum, Turkey). Microbial samples were taken from 43 patients (Group 1) with failed endodontic treatments and 36 patients (Group 2) with chronic apical periodontitis (primary endodontic infections). DNA was extracted from the samples by using a QIAamp® DNA mini-kit and analyzed with real-time PCR SYBR Green. RESULTS: E. faecalis was detected in 41 out of 79 patients, suggesting that it exists in not less than 61% of all endodontic infections when the proportion test (z= -1.645,